Interferon-I: The Pièce de Résistance of HIV-1 Transmission?. Issue 5 (May 2017) - Tully, Damien C.; Claiborne, Daniel T.; Allen, Todd M.
Abstract : Despite the extensive viral quasispecies that develops in an individual during the course of HIV-1 infection, transmission is typically established by a single donor viral variant. Recent studies now provide insight into the phenotypic properties influencing this selection process at transmission, including the contribution of resistance to type I interferons.